Lived Experiences of Nursing Home Residents in Korea - Soo Jung Chang, PhD, RN (Elsevier, 2013)
Purpose: The goal of the study was to understand the experiences of life among nursing home residents. Methods: Qualitative study was conducted using Colaizzi's phenomenological method. The participants were 11 people aged 76-96 years in two nursing homes in Korea. Results: Nine themes were identified: giving up on one self, growing apart from familiar relationships, perceiving the monotony of daily life as suffering, feeling anxious about one's future upon observing other residents, being dissatisfied with the lack of consideration for individualized care, developing interpersonal skills for communal life, missing the daily routines of their past lives, feeling optimistic about living in a nursing home, and having a strategy for the remainder of life in the nursing home. Conclusion: The results of this study confirmed the positive and negative emotions that elderly people typically experience while in nursing homes. Nurses should educate the families of nursing home residents, so that the family can better respect elderly people's opinions and provide them with adequate support. Furthermore, nurses must not only provide reliable support, resources and serve as advocates, but they must also pay more attention to the environment of the nursing home to make it feel like home to the elderly residents.